보육정책 변화에 따른 보육서비스 만족도에 미치는 영향 - 김가은(Gaeun Kim); 주정주(Jeong-Joo Joo); 박치면(Chimyen Park) (한국컴퓨터정보학회논문지, 2015)
This study is to test some expected performances coming from the introduction child care electronic voucher system, and suggest some policy implications. At first, this study established causal model on the expected performances of child care electronic voucher system, and then tested it through structural equation model on the base of survey. Survey was made through sampling employees of child care facilities in Gwangju Metropolitan City. This study showed that the expected effects of child care electronic voucher system are significant. This study suggested some implications basing on this analytical results. KCI Citation Count: 0